A Detailed Review Investigating the Mathematical Modeling of Solar Stills - Ayoobi, Ahmadreza; Ramezanizadeh, Mahdi (Frontiers in Energy Research, 2022)
In recent years providing potable water for humans has become a major problem, especially in rural and remote regions. In the last few decades, methods of providing potable water using solar radiation have proved that there are methods without negative impacts. Solar is a solution and attractive alternative to still non-potable water without adverse consequences on ecosystems. Researchers have presented the results of their investigations in journals, using experimental, numerical, and analytical forms through the study of solar still performance in native climatic conditions. This paper undertakes an extensive review of recent modeling processes in solar stills and the thermal models proposed and derived for different types of solar stills and the modifications recommended to enhance efficiency and performance. During the selection of appropriate geometry and belonging components, this evaluation demonstrates that numerous designs and characteristics are useful in terms of productivity and efficiency. According to the reviewed results, the definition of concentration ratio is a fundamental concept for evaluating the evaporative heat transfer coefficient in relation to the convective heat transfer coefficient. Employing phase change materials, the results reveal that a large mass of PCM produces less solar still productivity, whereas increasing the PCM to water mass ratio from 10 to 100 reduces productivity by up to 30%. Using a parabolic concentrator, results show that productivity can be increased by 56 and 38.5% in the winter and summer, respectively.